Global bibliometric analysis of conceptual metaphor research over the recent two decades - Zhao, Xia; Zheng, Yi; Zhao, Xincheng (Frontiers in Psychology, 2023)
This paper presents a comprehensive review of selected articles of studies on Conceptual Metaphor published during 2002–2022, as collected in the Web of Sciences database, from unique cognitive perspectives. Numerous publications and periodicals on this topic have been discovered. However, so far there have been few rigorous scientific mapping investigations. Therefore, this study aims to provide a bibliometric evaluation of its production during the recent two decades. Using the Web of Science Core Collection as its primary database, this study will examine the annual scientific output of Conceptual Metaphor, including its cited articles, sources, keywords, and research trends. Among the most notable findings are: Over the last two decades, (1) there has been a clear upward trend in Conceptual Metaphor studies;(2) the five most prominent research groups on Conceptual Metaphors are in the countries of Spain, the United States of America, China, Great Britain, and Russia; (3) the future study may focus on corpus linguistics, neurolinguistics, psychology, and critical discourse analysis. Interdisciplinary study may enhance the growth of Conceptual Metaphor.